The Dynamics of Resistance: Redefining Identity in Kiran Desai’s The Inheritance of Loss - Sharma Kandel, Bhanu Bhakta (Academia Journal of Humanities & Social Sciences, 2025)
Kiran Desai's The Inheritance of Loss intricately explores the complexities of cultural identity both as a tool of domination and a form of resistance within the context of postcolonial India and the global diaspora. The novel delves into the lives of characters grappling with the legacies of colonialism, globalization, and displacement, revealing how the power dynamics and historical forces shape cultural identity. Through the experiences of characters like Sai, Biju, and the judge, Desai illustrates how dominant cultures impose hierarchies and erasure while marginalized individuals and communities reclaim and redefine their identities as acts of resistance. The novel critiques the ways in which cultural identity is commodified and manipulated in a globalized world while also celebrating its potential to foster resilience and solidarity. Desai’s novel underscores the dual nature of cultural identity as a site of struggle and empowerment, reflecting the broader tensions of belonging and alienation in a rapidly changing world. Ethnic identity matters a lot when a certain group of people is forced to live under different forms of domination, such as demographic, economic, cultural, and political. The cultural concept of ‘ethnie’ or ethnicity has been used to discuss the literary products. The paper argues that Desai’s work offers a nuanced critique of the legacies of colonialism and the ongoing realities of cultural domination over the people who do not belong to one’s culture and language-speaking group. The main argument of this paper is that the minority or dominated group has to develop enough power to defy undue subjugation exercised by the majority or dominant group.